2016
DOI: 10.1021/acscatal.5b01933
|View full text |Cite
|
Sign up to set email alerts
|

PdZn Intermetallic Nanostructure with Pd–Zn–Pd Ensembles for Highly Active and Chemoselective Semi-Hydrogenation of Acetylene

Abstract: Intermetallic alloying of one active metal to another inert metal provides not only the improved dispersion of active centers but also a unique and homogeneous ensemble of active sites, thus offering new opportunities in a variety of reactions. Herein, we report that PdZn intermetallic nanostructure with Pd–Zn–Pd ensembles are both highly active and selective for the semihydrogenation of acetylene to ethylene, which is usually inaccessible due to the sequential hydrogenation to ethane. Microcalorimetric measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
298
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(327 citation statements)
references
References 75 publications
(121 reference statements)
17
298
0
Order By: Relevance
“…As shown in Figure S8, all alloyed PdAu catalysts delivered the higher activity compared with that of Pd or Au catalysts alone. This phenomenon of the PdAu alloyed catalysts with the improved hydrogenation activity was also observed in previous reports ,,,. With the increase Pd contents, the conversions of phenylacetylene were slightly increased form 43.3% to 49.5% for the alloy PdAu catalysts (Figure S8).…”
Section: Figuresupporting
confidence: 88%
See 1 more Smart Citation
“…As shown in Figure S8, all alloyed PdAu catalysts delivered the higher activity compared with that of Pd or Au catalysts alone. This phenomenon of the PdAu alloyed catalysts with the improved hydrogenation activity was also observed in previous reports ,,,. With the increase Pd contents, the conversions of phenylacetylene were slightly increased form 43.3% to 49.5% for the alloy PdAu catalysts (Figure S8).…”
Section: Figuresupporting
confidence: 88%
“…One viable approach to realize the selectively semi‐hydrogenated alkynes is to use bimetallic catalysts that combines the catalytically active metals with the second metals . Pd‐based catalysts modified by a second metal (e. g., Zn, Au, Ag, Pb, Cu) have been widely explored for the chemoselective semi‐hydrogenation of alkynes ,. This strategy with the controllable compositions of the alloyed metal catalysts can retain the high activity of Pd and increase catalytic selectivity at the same time.…”
Section: Figurementioning
confidence: 99%
“…Intermetallic materials with well‐defined structures and tunable compositions afford unique catalytic properties, and are thus highly desirable for heterogeneous catalysis . For instance, L1 0 ‐type PdZn with lattice parameters of a = b =4.0915 Å and c =3.3426 Å in space group P 4/ mmm , is regarded as a promising catalyst for methanol steam reforming (MSR), the water–gas shift reaction (WGS), alkane dehydrogenation, and selective hydrogenation reactions . The excellent catalytic performance of intermetallic PdZn is derived from reduction of the ZnO‐supported Pd, which give rise to unique electronic properties and structural stability.…”
Section: Figurementioning
confidence: 99%
“…Notably, with the incorporation of Ga, a slight red shift of the linear bond peak and the bridge bond peak is observed for 0.6Pd1.2Ga catalyst, which may result from strong electronic effects of Ga 2 O 3 on Pd nanoparticles. Similar results have suggested that electronic effects of Ga 2 O 3 on Pd leads to an increase of d‐orbital electron density of Pd, which exhibits a red shift in CO‐DRIFTS . To further confirm the electronic interaction between Ga and Pd species, XPS was conducted to investigate the chemical states of Pd and Ga species.…”
Section: Resultsmentioning
confidence: 99%